Vertical hydroponics: A future technology for urban horticulture - R Singh, S; Rajan, S (Indian Horticulture, 2022)
People have been forced to adopt a reliable crop-growing system that could provide ample opportunities to supplement fresh, safe, and healthy, pesticidefree, natural antioxidant-rich produce due to increased health consciousness, high incidence of fatal diseases due to excessive chemical use in horticultural crops, and inclination toward green living. Instead of helping to face the uncertainclimatic challenges in crop production, hydroponics, a technology of growing crops in nutrient solution, offers an opportunity for efficient use of natural resources, mitigation of malnutrition, more quality produce per unit area and time, where conventional farming is not possible due to water scarcity, degraded and sick soils.